2010
DOI: 10.1038/emboj.2010.140
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 recruitment of lysine methyltransferases regulates p53 transcriptional output

Abstract: MDM2 is a key regulator of the p53 tumor suppressor acting primarily as an E3 ubiquitin ligase to promote its degradation. MDM2 also inhibits p53 transcriptional activity by recruiting histone deacetylase and corepressors to p53. Here, we show that immunopurified MDM2 complexes have significant histone H3-K9 methyltransferase activity. The histone methyltransferases SUV39H1 and EHMT1 bind specifically to MDM2 but not to its homolog MDMX. MDM2 mediates formation of p53-SUV39H1/EHMT1 complex capable of methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 61 publications
6
59
0
Order By: Relevance
“…[3][4][5][6][7] However, MDM2 and MDMX genes have become increasingly prominent as key regulators of p53. 36,37 Consistently, overexpression of MDM2 and MDMX were observed in more than 40% of newly diagnosed myelomas using gene expression profile, suggesting the p53 inactivation in these cases (data not shown). Although we do not refute the previous conclusion established by the preponderance of literature, our results suggest that an extrinsic apoptotic signaling pathway is also a possible route for ATO to induce apoptosis.…”
Section: Discussionmentioning
confidence: 49%
“…[3][4][5][6][7] However, MDM2 and MDMX genes have become increasingly prominent as key regulators of p53. 36,37 Consistently, overexpression of MDM2 and MDMX were observed in more than 40% of newly diagnosed myelomas using gene expression profile, suggesting the p53 inactivation in these cases (data not shown). Although we do not refute the previous conclusion established by the preponderance of literature, our results suggest that an extrinsic apoptotic signaling pathway is also a possible route for ATO to induce apoptosis.…”
Section: Discussionmentioning
confidence: 49%
“…Indeed Ehmt2 has been found to bind and methylate lysine 373 of the murine p53 directly. 78 The Ehmt2-dependent methylation of p53 correlates with its inactivation, 79 thereby suggesting that when Ehmt2 function is lost, p53 may become primed for activation. However, it has been recently shown that one splice variant of hEHMT2 is also necessary to attenuate p53's transcriptional activation of its target genes in vitro.…”
Section: Ehmt2 In Cell Cycle Regulationmentioning
confidence: 99%
“…We tested this hypothesis using SUV39H1 as an example because of its efficient MDM2 binding (32). In vitro DNA binding assay showed that coexpression of SUV39H1 with MDM2 partially restored p53 DNA binding function (Fig.…”
Section: Arf Prevents P53 Conformational Change Andmentioning
confidence: 99%